Special composite alkali-activated curing agent for red clay and preparation method thereof

By using a composite alkali excitation system stimulated by sodium water glass, combined with ordinary silicate cement and metakaolin, the lack of mechanical properties of red clay in engineering projects and the problem of environmentally friendly reinforcement in engineering projects is solved, and the efficient and environmentally friendly red clay reinforcement effect is achieved. Reduced cement usage and carbon emissions.

CN119143444APending Publication Date: 2024-12-17KUNMING UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411289697.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

In engineering projects, red clay has problems such as insufficient mechanical properties, development of soil cracks, large shrinkage, hardness on top and softness on the bottom. The commonly used cement reinforcement methods are not environmentally friendly and difficult to meet the needs of green buildings.

Method used

Sodium water glass is used as an alkali exciter, combined with ordinary silicate cement and metakaolin to form a composite alkali excitation curing agent. By adjusting the modulus and dosage of the water glass, an efficient gelling material is generated to reinforce the red clay.

Benefits of technology

It significantly improves the compressive strength and shear strength of red clay, reduces the use of cement, reduces carbon dioxide emissions, and provides a green and environmentally friendly reinforcement solution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119143444A_ABST
    Figure CN119143444A_ABST
Patent Text Reader

Abstract

The invention relates to a special composite alkali-activated curing agent for red clay and a preparation method thereof, and belongs to the technical field of soil curing. The special composite alkali-activated curing agent for red clay is composed of ordinary Portland cement serving as a gelling component, metakaolin serving as an auxiliary gelling component and sodium water glass serving as an alkali activator, and according to the mass percent of natural red clay containing water, the cement accounts for 6%-15%, the metakaolin accounts for 1%-7%, and the sodium water glass accounts for 3%-9%. Compared with the method for directly reinforcing the red clay through pure cement, the method for curing the red clay through the novel composite alkali-activated system (cement, metakaolin and water glass) can obtain higher strength benefits. When the doping ratio of the cement is 12%, and the doping ratios of the metakaolin and the water glass are respectively 5% and 3%, the strength of the cured red clay is improved by 2.82 times compared with that of pure cement reinforcement.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a composite alkali-activated curing agent special for red clay and a preparation method thereof, belonging to the technical field of soil curing. Background Art

[0002] Red clay has engineering properties such as high water content, high plasticity and high swelling and shrinkage. Red clay in my country is mainly distributed in Guangxi, Yunnan, Hubei, Chongqing and other places. There are free oxides such as SiO2, Al2O3, and Fe2O3 in red clay. Although these free oxides have a certain cementing ability, which makes red clay have relatively good mechanical properties, it still cannot meet the needs of large-scale engineering projects. And because red clay has the characteristics of developed soil cracks, large shrinkage, and layered distribution of hard upper and soft lower, it is easy to cause engineering diseases such as cracking of municipal roads, uneven settlement of buildings and structures, and instability of slopes, so it is still regarded as problem soil. Cement soil mixing method is often used to reinforce red clay, but cement is not a green building material. Therefore, it is of great significance to seek high-performance environmentally friendly cementitious materials to partially or completely replace cement.

[0003] Geopolymer is a new type of inorganic gelling material with an amorphous three-dimensional network structure generated by active silicon-aluminum compounds through the action of alkali activators. It has the advantages of high strength, fast hardening, low carbon emissions and energy saving.

[0004] In view of this, the present invention proposes to use sodium water glass as an alkali activator, and cement and a metakaolin-based polymer as a cementitious material to reinforce red clay. Summary of the invention

[0005] In view of the problems and shortcomings of the above-mentioned prior art, the present invention provides a composite alkali-activated curing agent for red clay and a preparation method thereof. The material of the present invention is easily available, the production process is simple, it is easy to promote and use, and it is green and environmentally friendly.

[0006] The technical solution adopted by the present invention is:

[0007] The invention discloses a composite alkali-activated curing agent for red clay. The composite alkali-activated curing agent for red clay is composed of ordinary silicate cement as a gelling component, metakaolin as an auxiliary gelling component and sodium water glass as an alkali activator. Calculated by the mass percentage of the natural red clay containing water, the cement content is 6% to 15%, the metakaolin content is 1% to 7% and the sodium water glass content is 0% to 9%.

[0008] The composite alkali-activated curing agent for red clay is composed of a cementing component, ordinary silicate cement, an auxiliary cementing component, and an alkali-activated sodium water glass. Calculated by the mass percentage of the water-containing natural red clay, the cement content is 6% to 15%, the metakaolin content is 1% to 7%, and the sodium water glass content is 3% to 9%.

[0009] The main oxides of the ordinary Portland cement are CaO 61.748wt%, SiO2 17.174wt%, Al2O3 4.766wt% and MgO 3.6wt%; the main phase components are dicalcium silicate (C2S), tricalcium silicate (C3S), tricalcium aluminate (C3A) and tetracalcium aluminoferrite (C4AF).

[0010] The kaolin particle size is 1250 mesh (maximum particle size 10 μm) and the activity index is 110; the mass percentages of SiO2 and Al2O3 in the chemical composition of the kaolin are 47.13% and 43.26% respectively, and the phase composition contains a small amount of quartz (SiO2) and anatase (TiO2).

[0011] The sodium water glass has an initial modulus of 2.25M, a Baume degree of 50°Bé, and main components of 29.99% SiO2, 13.75% Na2O, and 56.26% H2O. Sodium hydroxide is used to adjust the modulus to 1.3M. The sodium water glass is prepared 24 hours in advance.

[0012] The sodium hydroxide concentration is 97 wt %.

[0013] A method for preparing a composite alkali-activated curing agent for red clay, comprising the following steps:

[0014] (1) adding 97 wt % sodium hydroxide to water glass with an initial modulus of 2.25 M to adjust the initial modulus from 2.25 M to 1.3 M, and leaving it to stand at room temperature for 24 hours to obtain sodium water glass;

[0015] (2) adding deionized water in an amount equal to the mass of cement to the sodium water glass in step (1), stirring and mixing to obtain a liquid mixture;

[0016] (3) Calculating the percentage by mass of the water-containing natural red clay, 6% to 15% of cement and 1% to 7% of metakaolin are stirred and mixed to obtain a solid phase mixture;

[0017] (4) The liquid mixture obtained in step (2) is mixed with the solid mixture obtained in step (3) in an amount of 0% to 9% calculated based on the mass percentage of the water-containing natural red clay, and the paste is obtained after stirring. The paste is a composite alkali-activated curing agent specifically for red clay.

[0018] The amount of sodium hydroxide added in step (1) is calculated according to the following formula:

[0019]

[0020] Where: m (NaOH) —Mass of NaOH required to be added, g;

[0021] W (1原) —Mass fraction of SiO2 in raw water glass;

[0022] M (目标模数) —Modulus of target water glass;

[0023] W (2原) —Mass fraction of Na2O in the original water glass;

[0024] 80—twice the relative molecular mass of NaOH;

[0025] 62—Relative molecular mass of Na2O.

[0026] In step (2), the mixing is performed for 2 to 3 minutes; in step (3), the mixing is performed for 1 to 2 minutes; and in step (4), the mixing is performed in a JJ-5 cement mortar mixer for 10 minutes.

[0027] The above modulus M can be calculated by the following formula, where M is the molar ratio of SiO2 to Na2O:

[0028]

[0029] Where: W1—mass fraction of SiO2;

[0030] W2—mass fraction of Na2O;

[0031] 1.032—Ratio of relative molecular mass of Na2O and SiO2.

[0032] The above-mentioned ordinary water glass may contain more high-polymer [SiO4] groups, which inhibit the occurrence of geopolymerization reaction or a large amount of OH in the solution of water glass. - The dissolution and polymerization process of the silicon-aluminum raw materials is aggravated, and the reaction of the metakaolin is hindered. Therefore, the present invention adopts sodium water glass with a modulus of 1.3M to generate more gelling products, improve the compressive strength and shear strength of the soil, and improve the performance of the red clay after solidification.

[0033] The principle of adding kaolin (MK) in the present invention is: (1) MK is rich in highly active amorphous SiO2 and Al2O3, has the characteristics of small particle size, large specific surface area and few impurities, and is a high-quality volcanic ash material and geopolymer raw material; (2) compared with traditional cement, the preparation process of kaolin is simple and the production energy consumption is low. The use of kaolin can improve the green sustainability of engineering construction; (3) adding kaolin as an auxiliary cementitious material to cement can not only make the cement hydrate more fully, but also participate in the subsequent volcanic ash reaction to generate more CSH, CAH and other cementing gels, thereby enhancing the overall bonding effect.

[0034] The principle of adding sodium water glass in the present invention is: (1) by activating the cementitious materials silicate and aluminate, sodium water glass helps to generate more cementitious products, thereby improving the compressive strength and shear strength of the soil; (2) since the CO2 emission in the production process of Portland cement is relatively high, the use of non-cement cementitious materials activated by sodium water glass can reduce the dependence on traditional Portland cement; (3) sodium water glass is generally low in cost and, as an economical and effective alkali activator, can control engineering costs while improving performance.

[0035] The beneficial effects of the present invention are:

[0036] (1) Compared with pure cement directly reinforcing red clay, the use of a new composite alkali-activated system (cement + kaolin + water glass) to solidify red clay can achieve higher strength gains. When the cement incorporation ratio is 12%, the kaolin and water glass incorporation ratios are 5% and 3% respectively, the strength of the solidified red clay is increased by 2.82 times compared with pure cement reinforcement.

[0037] (2) When the same requirements are met (unconfined compressive strength q u =2MPa), only 0.083 tons of cement (mixed with 5% MK and 3% water glass) is needed to solidify red clay per cubic meter, which can reduce carbon dioxide emissions by 38.76%. The composite alkali-activated system can be used as a transitional green and environmentally friendly curing agent.

[0038] (3) The raw materials of the curing agent include only three components: cement, metakaolin and sodium water glass. The preparation process is simple and can be easily promoted and applied in areas involving red clay projects. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 The present invention is a composite alkali-activated curing agent for red clay, with an MK mixing ratio of 5% and a sodium water glass mixing ratio of 0% to 9%. u Relationship diagram with cement consumption C;

[0040] Figure 2 The present invention is a composite alkali-activated curing agent for red clay, with an MK mixing ratio of 7% and a sodium water glass mixing ratio of 0% to 9%. u Relationship diagram with cement consumption C. DETAILED DESCRIPTION

[0041] The present invention will be further described below in conjunction with the accompanying drawings and specific implementation methods.

[0042] Example 1

[0043] The special composite alkali-activated curing agent for red clay is composed of ordinary silicate cement as a gelling component, metakaolin as an auxiliary gelling component and sodium water glass as an alkali activator. Calculated by the mass percentage of natural red clay containing water, the cement is added in an amount of 6% to 15%, the metakaolin is added in an amount of 1% to 7% and the sodium water glass is added in an amount of 0%, and water of the same mass as that of the cement is added.

[0044] The main oxides of ordinary Portland cement (PO42.5 grade) are CaO61.748wt%, SiO217.174wt%, Al2O34.766wt% and MgO3.6wt%; the main phase components are dicalcium silicate (C2S), tricalcium silicate (C3S), tricalcium aluminate (C3A) and tetracalcium aluminoferrite (C4AF).

[0045] The particle size of the metakaolin is 1250 mesh (maximum particle size 10 μm) and the activity index is 110; the mass percentages of SiO2 and Al2O3 in the chemical composition of the metakaolin are 47.13% and 43.26% respectively, and the phase composition contains a small amount of quartz (SiO2) and anatase (TiO2).

[0046] The initial modulus of sodium water glass is 2.25M, the Baume degree is 50°Bé, and the main components are 29.99% SiO2, 13.75% Na2O and 56.26% H2O; the modulus is adjusted to 1.3M using sodium hydroxide; the sodium water glass is configured 24 hours in advance.

[0047] The concentration of sodium hydroxide is 97wt%.

[0048] The preparation method of the composite alkali-activated curing agent for red clay comprises the following steps:

[0049] (1) Stirring and mixing deionized water in an amount equal to the mass of cement to obtain a liquid mixture;

[0050] (2) Calculating the percentage by mass of the water-containing natural red clay, 6% to 15% of cement and 1% to 7% of metakaolin are stirred and mixed for 1 to 2 minutes to obtain a solid phase mixture;

[0051] (3) The liquid mixture obtained in step (2) is mixed with the solid mixture obtained in step (2) in an amount of 0% to 9% calculated based on the mass percentage of the natural red clay containing water, and stirred in a JJ-5 cement mortar mixer for 10 minutes to obtain a paste, which is a composite alkali-activated curing agent specifically for red clay.

[0052] The above-mentioned curing agent was added into red clay with a porosity ratio of 1.43, an unconfined compressive strength of 162.22 kPa, a moisture content of 34%, and liquid limit and plastic limit of 59.8% and 32.2% respectively.

[0053] The red clay mixed with curing agent was filled into a 70.7mm×70.7mm×70.7mm cubic mold in three times, and then the cubic test mold was fixed on a vibration table and vibrated for no less than 2 minutes. After vibration, the excess mixture on the top of the test mold was scraped off and immediately covered with plastic wrap to prevent moisture evaporation to ensure that the sample was not damaged or deformed. The mold was removed after 24 hours.

[0054] The specimens were placed in a standard curing room (temperature controlled at 20±2°C, relative humidity 95±2%) for curing. After 28 days of curing, the unconfined compressive strength test was carried out according to the test method of GB / T 50123-2019, and the test results are as follows.

[0055] Table 1: Relationship between unconfined compressive strength and cement and kaolin mixing ratio

[0056]

[0057]

[0058] As shown in Table 1, the strength of the solidified soil increases significantly with the increase of cement mixing ratio. When the cement mixing ratio reaches 15%, the strength of the solidified soil is as high as 2.40Mpa. However, when the cement mixing ratio is constant, the strength of the solidified soil increases first and then decreases with the increase of the kaolin mixing ratio. There is an optimal value for its mixing ratio. When the cement mixing ratio is 9%, 12% and 15%, the optimal mixing ratio of kaolin is 3%. Under the same cement mixing ratio, the cement + kaolin auxiliary cementitious system solidified soil can obtain higher strength, which reduces the amount of cement from another perspective.

[0059] Example 2

[0060] The special composite alkali-activated curing agent for red clay is composed of ordinary silicate cement as a gelling component, metakaolin as an auxiliary gelling component and sodium water glass as an alkali activator. Calculated by the mass percentage of natural red clay containing water, the cement is added in an amount of 12%, the metakaolin is added in an amount of 1% to 7% and the sodium water glass is added in an amount of 0% to 9%, and water of the same mass as that of the cement is added.

[0061] The main oxides of ordinary Portland cement (PO42.5 grade) are CaO61.748wt%, SiO217.174wt%, Al2O34.766wt% and MgO3.6wt%; the main phase components are dicalcium silicate (C2S), tricalcium silicate (C3S), tricalcium aluminate (C3A) and tetracalcium aluminoferrite (C4AF).

[0062] The particle size of the metakaolin is 1250 mesh (maximum particle size 10 μm) and the activity index is 110; the mass percentages of SiO2 and Al2O3 in the chemical composition of the metakaolin are 47.13% and 43.26% respectively, and the phase composition contains a small amount of quartz (SiO2) and anatase (TiO2).

[0063] The initial modulus of sodium water glass is 2.25M, the Baume degree is 50°Bé, and the main components are 29.99% SiO2, 13.75% Na2O and 56.26% H2O; the modulus is adjusted to 1.3M using sodium hydroxide; the sodium water glass is configured 24 hours in advance.

[0064] The concentration of sodium hydroxide is 97wt%.

[0065] The preparation method of the composite alkali-activated curing agent for red clay comprises the following steps:

[0066] (1) adding 97 wt % sodium hydroxide to water glass with an initial modulus of 2.25 M to adjust the initial modulus from 2.25 M to 1.3 M, and leaving it to stand at room temperature for 24 hours to obtain sodium water glass;

[0067] (2) adding deionized water in an amount equal to the mass of cement to the sodium water glass in step (1), stirring and mixing for 2 to 3 minutes to obtain a liquid mixture;

[0068] (3) Calculating the mass percentage of the water-containing natural red clay, 12% of cement and 1% to 7% of metakaolin are stirred and mixed for 1 to 2 minutes to obtain a solid phase mixture;

[0069] (4) The liquid mixture obtained in step (2) is mixed with the solid mixture obtained in step (3) in an amount of 0% to 9% calculated based on the mass percentage of the natural red clay containing water, and stirred in a JJ-5 cement mortar mixer for 10 minutes to obtain a paste, which is a composite alkali-activated curing agent specifically for red clay.

[0070] The red clay mixed with curing agent was filled into a 70.7mm×70.7mm×70.7mm cubic mold in three times, and then the cubic test mold was fixed on a vibration table and vibrated for no less than 2 minutes. After vibration, the excess mixture on the top of the test mold was scraped off and immediately covered with plastic wrap to prevent moisture evaporation to ensure that the sample was not damaged or deformed. The mold was removed after 24 hours.

[0071] The specimens were placed in a standard curing room (temperature controlled at 20±2°C, relative humidity 95±2%) for curing. After 28 days of curing, the unconfined compressive strength test was carried out according to the test method of GB / T 50123-2019, and the test results are as follows.

[0072] Table 2: Relationship between the unconfined compressive strength of stabilized soil and the sodium water glass incorporation ratio

[0073] Strength / MPa Metakaolin 1% Metakaolin 3% Metakaolin 5% Metakaolin 7% Sodium water glass 0% 2.13 2.18 1.45 1.54 Sodium water glass 3% 3.75 3.63 4.31 4.01 Sodium water glass 5% 3.88 3.3 3.76 2.95 Sodium water glass 7% 4.24 3.62 4.16 3.17 Sodium water glass 9% 3.44 3.68 4.07 3.6

[0074] As shown in Table 2, the addition of sodium water glass greatly improves the strength of the solidified red clay, which indicates that sodium water glass stimulates the chemical activity of metakaolin and promotes the formation of geopolymer gel, thereby improving the strength of cement-solidified soil. When the cement incorporation ratio is 12%, the strength of the solidified red clay is the highest when the incorporation ratios of metakaolin and sodium water glass are 5% and 3% respectively, reaching 4.31Mpa.

[0075] Example 3

[0076] The special composite alkali-activated curing agent for red clay is composed of ordinary silicate cement as a gelling component, metakaolin as an auxiliary gelling component and sodium water glass as an alkali activator. Calculated by the mass percentage of natural red clay containing water, the cement, metakaolin and sodium water glass in an amount of 6% to 15%, 5% and 3% respectively are added, and water in an amount equal to the mass of the cement is added.

[0077] The main oxides of ordinary Portland cement (PO42.5 grade) are CaO61.748wt%, SiO217.174wt%, Al2O34.766wt% and MgO3.6wt%; the main phase components are dicalcium silicate (C2S), tricalcium silicate (C3S), tricalcium aluminate (C3A) and tetracalcium aluminoferrite (C4AF).

[0078] The particle size of the metakaolin is 1250 mesh (maximum particle size 10 μm) and the activity index is 110; the mass percentages of SiO2 and Al2O3 in the chemical composition of the metakaolin are 47.13% and 43.26% respectively, and the phase composition contains a small amount of quartz (SiO2) and anatase (TiO2).

[0079] The initial modulus of sodium water glass is 2.25M, the Baume degree is 50°Bé, and the main components are 29.99% SiO2, 13.75% Na2O and 56.26% H2O; the modulus is adjusted to 1.3M using sodium hydroxide; the sodium water glass is configured 24 hours in advance.

[0080] The concentration of sodium hydroxide is 97wt%.

[0081] The preparation method of the composite alkali-activated curing agent for red clay comprises the following steps:

[0082] (1) adding 97 wt % sodium hydroxide to water glass with an initial modulus of 2.25 M to adjust the initial modulus from 2.25 M to 1.3 M, and leaving it to stand at room temperature for 24 hours to obtain sodium water glass;

[0083] (2) adding deionized water in an amount equal to the mass of cement to the sodium water glass in step (1), stirring and mixing for 2 to 3 minutes to obtain a liquid mixture;

[0084] (3) Calculating the percentage by mass of the water-containing natural red clay, 6% to 15% of cement and 5% of metakaolin are stirred and mixed for 1 to 2 minutes to obtain a solid phase mixture;

[0085] (4) The liquid mixture obtained in step (2) is mixed with the solid mixture obtained in step (3) at a dosage of 3% calculated based on the mass percentage of the natural red clay containing water, and stirred in a JJ-5 cement mortar mixer for 10 minutes to obtain a paste, which is a composite alkali-activated curing agent specifically for red clay.

[0086] The red clay mixed with curing agent was filled into a 70.7mm×70.7mm×70.7mm cubic mold in three times, and then the cubic test mold was fixed on a vibration table and vibrated for no less than 2 minutes. After vibration, the excess mixture on the top of the test mold was scraped off and immediately covered with plastic wrap to prevent moisture evaporation to ensure that the sample was not damaged or deformed. The mold was removed after 24 hours.

[0087] The samples were then placed in a standard curing room (temperature controlled at 20±2°C, relative humidity 95±2%) for curing. After 28 days of curing, direct shear tests were performed on the ring knife samples using a SDJ-2 electric strain-controlled direct shear apparatus under vertical pressure conditions of 100 kPa, 200 kPa, 300 kPa, and 400 kPa, respectively.

[0088] Table 3: Cohesion of red clay solidified by composite alkali activation system

[0089]

[0090] Table 4: Internal friction angle of red clay solidified by composite alkali activation system

[0091]

[0092] It can be seen from Tables 3 and 4 that the greater the amount of cement added, the greater the cohesion of the sample, and the cohesion of the red clay improved by the metakaolin-based curing agent increased from 16.3 kPa in the natural state to 170.85, 284.75, 309.15 and 326.8 kPa, respectively, with a significant improvement effect. The internal friction angle of the red clay used in the test was 6.9° in the natural state, and it was above 15° after curing with different systems. Since there are many soil particles in the red clay, the cementing gel can contribute part of the mechanical bite force when resisting shear after bonding it. In the composite alkali-activated system, the cement content reached 2.82, 6.69, 7.45 and 8.36 times that of the natural soil, respectively.

[0093] Example 4

[0094] The special composite alkali-activated curing agent for red clay is composed of ordinary silicate cement as a gelling component, metakaolin as an auxiliary gelling component and sodium water glass as an alkali activator. Calculated by the mass percentage of natural red clay containing water, the cement is added in an amount of 12%, the metakaolin is added in an amount of 1% to 7% and the sodium water glass is added in an amount of 3% to 9%, and water of the same mass as that of the cement is added.

[0095] The main oxides of ordinary Portland cement (PO42.5 grade) are CaO61.748wt%, SiO217.174wt%, Al2O34.766wt% and MgO3.6wt%; the main phase components are dicalcium silicate (C2S), tricalcium silicate (C3S), tricalcium aluminate (C3A) and tetracalcium aluminoferrite (C4AF).

[0096] The particle size of the metakaolin is 1250 mesh (maximum particle size 10 μm) and the activity index is 110; the mass percentages of SiO2 and Al2O3 in the chemical composition of the metakaolin are 47.13% and 43.26% respectively, and the phase composition contains a small amount of quartz (SiO2) and anatase (TiO2).

[0097] The initial modulus of sodium water glass is 2.25M, the Baume degree is 50°Bé, and the main components are 29.99% SiO2, 13.75% Na2O and 56.26% H2O; the modulus is adjusted to 1.3M using sodium hydroxide; the sodium water glass is configured 24 hours in advance.

[0098] The concentration of sodium hydroxide is 97wt%.

[0099] The preparation method of the composite alkali-activated curing agent for red clay comprises the following steps:

[0100] (1) adding 97 wt % sodium hydroxide to water glass with an initial modulus of 2.25 M to adjust the initial modulus from 2.25 M to 1.3 M, and leaving it to stand at room temperature for 24 hours to obtain sodium water glass;

[0101] (2) adding deionized water in an amount equal to the mass of cement to the sodium water glass in step (1), stirring and mixing for 2 to 3 minutes to obtain a liquid mixture;

[0102] (3) Calculating the mass percentage of the water-containing natural red clay, 12% of cement and 1% to 7% of metakaolin are stirred and mixed for 1 to 2 minutes to obtain a solid phase mixture;

[0103] (4) The liquid mixture obtained in step (2) is mixed with the solid mixture obtained in step (3) in an amount of 3% to 9% calculated based on the mass percentage of the natural red clay containing water, and stirred in a JJ-5 cement mortar mixer for 10 minutes to obtain a paste, which is a composite alkali-activated curing agent specifically for red clay.

[0104] The prepared curing agent was added into red clay with a porosity ratio of 1.43, an unconfined compressive strength of 162.22 kPa, a moisture content of 34%, and liquid limit and plastic limit of 59.8% and 32.2%, respectively.

[0105] Fill the red clay mixed with curing agent into a cubic mold of 70.7mm×70.7mm×70.7mm, then fix the test mold on a vibration table and vibrate it for no less than 2 minutes. After vibration, scrape off the excess mixture on the top of the test mold and immediately cover it with plastic wrap to prevent moisture evaporation to ensure that the sample is not damaged or deformed. Remove the mold after 24 hours.

[0106] The samples were placed in a standard curing room (temperature controlled at 20±2°C, relative humidity 95±2%) for curing. After 28 days of curing, the mass of the cured samples was weighed, and their density was calculated. The moisture content was tested, and the dry density of the samples was calculated from the density and moisture content.

[0107] Table 5: Relationship between dry density of solidified red clay and the ratio of kaolin and sodium water glass

[0108] <![CDATA[Dry density / g·cm 3 > Metakaolin 1% Metakaolin 3% Metakaolin 5% Metakaolin 7% Sodium water glass 0% 1.30 1.32 1.32 1.33 Sodium water glass 3% 1.35 1.36 1.35 1.33 Sodium water glass 5% 1.32 1.34 1.34 1.29 Sodium water glass 7% 1.33 1.36 1.35 1.30 Sodium water glass 9% 1.31 1.33 1.31 1.28

[0109] The dry density of pure cement-stabilized soil is 1.289. As shown in Table 5, compared with pure cement-stabilized soil, the dry density of the stabilized red clay improved by kaolin stabilizer has basically increased, which indicates that the density of the stabilized soil structure has been effectively improved. Under the same sodium water glass incorporation ratio, the dry density of the stabilized soil shows a trend of first increasing and then decreasing with the increase of kaolin incorporation ratio, which is consistent with the change law of strength. When the kaolin incorporation ratio is consistent, the dry density of the stabilized soil shows a trend of first increasing and then decreasing with the increase of water glass incorporation ratio. When the incorporation ratio is 3%, the filling effect is the best. The incorporation of sodium water glass generates gel substances such as (N,C)-ASH and C-(A)-SH, thereby improving its bonding and filling effects and increasing the density.

[0110] Comparative Example 1

[0111] This comparative example 1 is the same as Example 2, except that the sodium water glass in Example 2 is replaced by water glass with an initial modulus of 2.25M.

[0112] The curing agent, the composite alkali-activated curing agent special for red clay, is composed of a gelling component, ordinary silicate cement, an auxiliary gelling component, metakaolin, and an alkali-activated sodium water glass. Calculated by the mass percentage of the water-containing natural red clay, the cement content is 12%, the metakaolin content is 1% to 7%, and the water glass content is 0% to 9%.

[0113] The preparation method of the composite alkali-activated curing agent for red clay comprises the following steps:

[0114] (1) adding water glass with an initial modulus of 2.25M to deionized water of the same mass as cement, stirring and mixing for 2 to 3 minutes to obtain a liquid mixture;

[0115] (2) Calculating the percentage by mass of the water-containing natural red clay, 12% of cement and 1% to 7% of kaolin are stirred and mixed for 1 to 2 minutes to obtain a solid phase mixture;

[0116] (3) The liquid mixture obtained in step (1) is mixed with the solid mixture obtained in step (2) in an amount of 0% to 9% calculated based on the mass percentage of the natural red clay containing water, and stirred in a JJ-5 cement mortar mixer for 10 minutes to obtain a paste, which is a composite alkali-activated curing agent specifically for red clay.

[0117] The red clay mixed with curing agent was filled into a 70.7mm×70.7mm×70.7mm cubic mold in three times, and then the cubic test mold was fixed on a vibration table and vibrated for no less than 2 minutes. After vibration, the excess mixture on the top of the test mold was scraped off and immediately covered with plastic wrap to prevent moisture evaporation to ensure that the sample was not damaged or deformed. The mold was removed after 24 hours.

[0118] The specimens were placed in a standard curing room (temperature controlled at 20±2°C, relative humidity 95±2%) for curing. After 28 days of curing, the unconfined compressive strength test method in GB / T 50123-2019 was used for testing. The test results are shown in Table 6 below.

[0119] Table 6 Unconfined compressive strength of soil stabilized with water glass as activator

[0120] Strength / MPa Metakaolin 1% Metakaolin 3% Metakaolin 5% Metakaolin 7% Water glass 0% 2.13 2.18 1.45 1.54 Water glass 3% 1.87 1.72 2.18 1.93 Water glass 5% 1.95 1.60 1.89 1.43 Water glass 7% 2.07 1.72 1.96 1.57 Water glass 9% 1.73 1.80 1.93 1.72

[0121] From the comparison between Table 2 and Table 6, it can be seen that ordinary water glass may contain more high-polymerized [SiO4] groups, which inhibit the occurrence of geopolymerization reaction or a large amount of OH in the solution of water glass. - The dissolution and polymerization process of the silicon-aluminum raw materials is aggravated, and the reaction of the metakaolin is hindered. Therefore, the present invention adopts sodium water glass with a modulus of 1.3M to generate more gelling products, improve the compressive strength and shear strength of the soil, and improve the strength performance of the red clay after solidification.

[0122] By statistically analyzing the solidification of pure cement and the composite alkali activation system for red clay of the present invention for 1m 3 The strength of the red clay sample and the amount of cement consumed were used, and the unconfined compressive strength q was established by linear fitting. u The relationship with cement consumption C is as follows: Figure 1 and Figure 2 As shown. The fitting curves of each group of red clay solidified by the composite alkali activation system (after adding water glass) are all above the pure cement group, indicating that if the solidified sample is to achieve the same strength, the composite alkali activation system of cement + MK + sodium water glass consumes less cement. Table 7 statistics the amount of cement consumed by the optimal ratio of the composite alkali activation system with different MK addition ratios when the given strength is reached. It can be seen from the table that when the same strength is achieved, the cement consumption of the composite alkali activation system solidification scheme is much less than that of the pure cement system. When the soil strength reaches 2MPa, it can reduce carbon emissions by more than 35%. The preparation process of the geopolymer raw material MK is simple, the calcination temperature is low and the energy consumption is low. As a green and environmentally friendly material, it reduces CO2 emissions and can be used as a transitional green and environmentally friendly curing agent.

[0123] Table 7 Cement consumption and carbon emission reduction percentage of each optimal solution at a given strength

[0124]

[0125] The specific implementation modes of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited to the above implementation modes, and various changes can be made within the knowledge scope of ordinary technicians in this field without departing from the purpose of the present invention.

Claims

1. A composite alkali-activated curing agent for red clay, characterized in that: The composite alkali-activated curing agent for red clay is composed of a cementing component, ordinary silicate cement, an auxiliary cementing component, and an alkali-activated sodium water glass. Calculated by the mass percentage of the natural red clay containing water, the cement content is 6% to 15%, the metakaolin content is 1% to 7%, and the sodium water glass content is 0% to 9%.

2. The composite alkali-activated curing agent for red clay according to claim 1, characterized in that: The composite alkali-activated curing agent for red clay is composed of a cementing component, ordinary silicate cement, an auxiliary cementing component, and an alkali-activated sodium water glass. Calculated by the mass percentage of the water-containing natural red clay, the cement content is 6% to 15%, the metakaolin content is 1% to 7%, and the sodium water glass content is 3% to 9%.

3. The composite alkali-activated curing agent for red clay according to claim 1, characterized in that: The main oxides of the ordinary Portland cement are CaO 61.748wt%, SiO2 17.174wt%, Al2O3 4.766wt% and MgO 3.6wt%; the main phase components are dicalcium silicate, tricalcium silicate, tricalcium aluminate and tetracalcium aluminoferrite.

4. The composite alkali-activated curing agent for red clay according to claim 1, characterized in that: The particle size of the metakaolin is 1250 meshes, and the activity index is 110; the mass percentages of SiO2 and Al2O3 in the chemical composition of the metakaolin are 47.13% and 43.26% respectively, and the phase composition contains a small amount of quartz and anatase.

5. The composite alkali-activated curing agent for red clay according to claim 1, characterized in that: The sodium water glass has an initial modulus of 2.25M, a Baume degree of 50°Bé, and main components of 29.99% SiO2, 13.75% Na2O, and 56.26% H2O. The modulus is adjusted to 1.3M using sodium hydroxide. The sodium water glass is prepared 24 hours in advance.

6. The composite alkali-activated curing agent for red clay according to claim 5, characterized in that: The sodium hydroxide concentration is 97 wt %.

7. A method for preparing a composite alkali-activated curing agent for red clay according to claim 1, characterized in that: The steps include: (1) adding 97 wt % sodium hydroxide to water glass with an initial modulus of 2.25 M to adjust the initial modulus from 2.25 M to 1.3 M, and leaving it to stand at room temperature for 24 hours to obtain sodium water glass; (2) adding deionized water in an amount equal to the mass of cement to the sodium water glass in step (1), stirring and mixing to obtain a liquid mixture; (3) Calculating the percentage by mass of the water-containing natural red clay, 6% to 15% of cement and 1% to 7% of metakaolin are stirred and mixed to obtain a solid phase mixture; (4) The liquid mixture obtained in step (2) is mixed with the solid mixture obtained in step (3) in an amount of 0% to 9% calculated based on the mass percentage of the water-containing natural red clay, and the paste is obtained after stirring. The paste is a composite alkali-activated curing agent specifically for red clay.

8. The method for preparing the composite alkali-activated curing agent for red clay according to claim 7, characterized in that: The amount of sodium hydroxide added in step (1) is calculated according to the following formula: Where: m (NaOH) —Mass of NaOH required to be added, g; W (1原) —Mass fraction of SiO2 in raw water glass; M (目标模数) —Modulus of target water glass; W (2原) —Mass fraction of Na2O in the original water glass; 80—twice the relative molecular mass of NaOH; 62—Relative molecular mass of Na2O.

9. The method for preparing the composite alkali-activated curing agent for red clay according to claim 7, characterized in that: In step (2), the mixing is performed for 2 to 3 minutes; in step (3), the mixing is performed for 1 to 2 minutes; and in step (4), the mixing is performed in a JJ-5 cement mortar mixer for 10 minutes.